2018
DOI: 10.14227/dt250318p52
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Release Testing Methodology and Variability with the Vertical Diffusion Cell (VDC)

Abstract: In vitro release test (IVRT) using the vertical diffusion cell (VDC) is a well-established method to evaluate the performance of a topical dosage form and to better understand the physicochemical characteristics of the product. The VDC is the most frequently used apparatus to measure drug release from semisolid products and has been in use for more than fifty years; however, the technique is often hampered by high variability and inadequate reproducibility. Various method parameters influence drug release and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 19 publications
1
7
0
Order By: Relevance
“…The solubility of MCZ in the receptor medium was 3671 µg/mL (±60.24) which was more than 10 times higher than the highest measured concentration in the samples obtained during the method validation experiment (150 µg/mL). The results confirmed that the solubility of MCZ in the receptor medium was sufficiently high to prevent saturation effects and to ensure sink conditions [19].…”
Section: Mcz Solubility In the Receptor Mediumsupporting
confidence: 70%
See 1 more Smart Citation
“…The solubility of MCZ in the receptor medium was 3671 µg/mL (±60.24) which was more than 10 times higher than the highest measured concentration in the samples obtained during the method validation experiment (150 µg/mL). The results confirmed that the solubility of MCZ in the receptor medium was sufficiently high to prevent saturation effects and to ensure sink conditions [19].…”
Section: Mcz Solubility In the Receptor Mediumsupporting
confidence: 70%
“…Aliquots of the supernatant were withdrawn, filtered, diluted and analysed to determine the concentration of the dissolved MCZ. Ideally, the solubility of the drug should be > 10 times the maximum expected concentration of the drug in the receptor medium throughout the IVRT run [19]. A duplicate set of control MCZ solutions without membranes was evaluated in parallel.…”
Section: Mcz Solubility In the Receptor Mediummentioning
confidence: 99%
“…The receptor medium that had the most favorable outcome was ethanol:water (55/45 v/v), where the mean HCA solubility was 4447.4 µg/mL (CV = 6.38%). The latter concentration was more than 10 times the maximum expected concentration, as recommended (18).…”
Section: Membrane Screening and Receptor Fluid Selectionmentioning
confidence: 66%
“…Although the observed solubilities of MTZ were >10 times the maximum expected concentration, as recommended [9], 0.9% NaCl solution was chosen as the receptor medium for subsequent studies, as it more appropriately reflects physiological conditions and is inexpensive and readily available. All the membranes except the Mixed Cellulose Ester membrane showed an acceptable recovery, indicating low MTZ binding.…”
Section: Discussionmentioning
confidence: 99%
“…Until recently, however, amongst the numerous publications involving the application of IVRT, comprehensive validation of IVRT systems and methods have been conspicuously absent from the literature. Although various efforts [8][9][10] have been made by several researchers to develop a standardized method to measure in vitro drug release from a product using diffusion cells, a comprehensive validation that would be generally applicable to all topical dermatological dosage forms has only recently been published [11]. This is essential to ensure that the developed IVRT method and the associated system has the necessary discriminatory capabilities to determine "sameness" between products and also, more importantly, differences, which may affect clinical performance.…”
Section: Introductionmentioning
confidence: 99%